Medalha e continência: uma etnografia de atletas militares no esporte de representação nacional - Thomaz, Diego Wander (2019)
This research is based on anthropological analysis of high performance athletes linked to a military program to encourage national representative sports, the so-called military athletes. This is the High Performance Athletes Program, signed through an agreement between the Ministries of Sport and Defense, with the objective of incorporating top athletes in the Armed Forces to compete in national and international sports competitions. For this, I gathered information on the official websites of the Ministries, the Olympic Committee, the Armed Forces, among others, through materials and documents about the program available in them. In addition, I attended Pinheiros Sport Club, which, being a private and paisano sports club, has in its staff a considerable number of military athletes, previously belonging to the club; professional ties, in this case, are not exclusive. Finally, I conducted interviews with military athletes in order to produce primary data for the proposed ethnography, in addition to observation and description. The objective was to verify how sporting and militarization processes occur side by side in this interface between sport and barracks, which keep a strong historical relationship, through notions such as the construction of the body and the sportive-military person in these professional careers, mobilizing athletes, clubs, federations, committees, government and the military in the composition and political management of a national sports system.